2011
DOI: 10.1103/physrevd.84.023518
|View full text |Cite
|
Sign up to set email alerts
|

Constraining variations in the fine structure constant in the presence of early dark energy

Abstract: We discuss present and future cosmological constraints on variations of the fine structure constant induced by an early dark energy component having the simplest allowed (linear) coupling to electromagnetism. We find that current cosmological data show no variation of the fine structure constant at recombination with respect to the present-day value, with = 0 ¼ 0:975 AE 0:020 at 95% C.L., constraining the energy density in early dark energy to e < 0:060 at 95% C.L. Moreover, we consider constraints on the para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…These bounds indicate a good agreement with the forecast of Planck and CMBPol experiments [33] as well as with the upper bound provided by the constraints on the variation in the fine structure constant [35]. As we have already mentioned, the presence of dark energy at BBN era should not disturb the observed Helium abundance in the universe which is regarded as one of the major evidence in supporting the big bang theory.…”
Section: Discussionsupporting
confidence: 73%
“…These bounds indicate a good agreement with the forecast of Planck and CMBPol experiments [33] as well as with the upper bound provided by the constraints on the variation in the fine structure constant [35]. As we have already mentioned, the presence of dark energy at BBN era should not disturb the observed Helium abundance in the universe which is regarded as one of the major evidence in supporting the big bang theory.…”
Section: Discussionsupporting
confidence: 73%
“…With these assumptions one can explicitly relate the evolution of α to that of dark energy, as in [179] whose derivation we summarize here. The evolution of α can be written ∆α…”
Section: Canonical Scalar Fieldsmentioning
confidence: 99%
“…while in [179] an independent few-percent constraint on this coupling was obtained using CMB and large-scale structure data in combination with direct measurements of the present-day Hubble parameter. We note that there is in principle an additional source term driving the evolution of the scalar field, due to a F 2 B ′ F term.…”
Section: Canonical Scalar Fieldsmentioning
confidence: 99%
“…The variation of μ and α with time or scalefactor is related to the evolution of the dark energy density and the dark energy equation of state (Calabrese et al 2011;Thompson 2012). The QCD scale as a function of the scalefactor a in slow roll quintessence is examined as an example of such evolution.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Independently Calabrese et al (2011) for α and Thompson (2012) for μ showed that for a rolling scalar field φ in a potential V(φ) with a quintessence dark energy equation of state…”
Section: Q U I N T E S S E N C E E X a M P L E O F Qcd E Vo L U T I O Nmentioning
confidence: 99%